Encyclopedia of the philosophy of law and social philosophy - Sellers, M. N. S.; Kirste, Stephan (Springer Netherlands, 2023)
Applied Legal Philosophy -- Contemporary Legal Philosophy -- Formal Structure of Law -- History of the Philosophy of Law and Social Philosophy -- Justice -- Legal Institutions -- Legal Methods -- Legal Systems -- Liberty and Equality -- Schools of Legal Thought -- Social Philosophy -- The Common Good.-The Science of the Law and Social Sciences -- Theory of Rights.
Keywords: Sozialphilosophie; Rechtsphilosophie